Economics versus Literature (L'economia contro la letteratura) - William A. Jackson (Narrativa, 2020)
Economics has always had a difficult relationship with literature. Although early economists such as Adam Smith adopted a literary approach, pressures soon emerged to develop formal theory imitating natural sciences. A key aim was to attain scientific status and avoid comparison with literary studies, history and the rest of the humanities. By the twentieth century, economics had become professionalised into a self-contained discipline expressed in mathematical language and making little effort to communicate with the general reader. The current paper looks at this anti-literary trend in economics and considers its implications. Separation of economics from literature is unhelpful, as it plays down the cultural and historical aspects of economics, as well as keeping economic discussion aloof from wider discourse. Literary authors who write about economics are regarded as providing amateur commentary with no relevance for the discipline; economists who write for a non-specialist audience are regarded as straying outside serious academic work. The anti-literary bent of economics has narrowed its perspective – increased literary input bringing it closer to the humanities could improve its critical and interpretative capacities.
Keywords: A12; A14; B41; B50; Z10; 330; economics; literature; mathematics; interpretative methods; pluralism